Interaction in e learning environment: does it fulfill with Islamic teaching? - Syed Hassan, Sharifah Sariah; Shirin, Hasina Banu; Islam, Mohammad Serazul (University Malaya, 2014)
Interactions in e-learning are very important in delivering updates, information and course contents. With the advancement of communications technology such as Learning Management System (LMS), social network sites (SNS) and mobile technology, communication is no longer a barrier for interacting with lecturers and peers. In Moore’s Transactional Distance Theory, interactions are categorized under student-student, student-lecturer and student-content. When these interactions are addressed, effective learning takes place. On the hand, Ghazali’s framework of four rungs of consciousness relates intrinsic motivation to qalb, ruh, aql and nafs. When these intrinsic elements are fulfilled, students are able to reach the highest learning accomplishment namely wisdom (Hikmah) and well-being. This present study seeks to explore the practice of interactions among e-learning students in the context of Moore’s distance theory that also conform to the Islamic teaching in an e-learning environment. For this qualitative research, two selected e-learning students (from the B.Ed. degree program) at an Islamic University in Malaysia were interviewed as participants. The results show that students perceive the rigorous importance of practicing interaction to enrich learning in the e-learning environment of a university. Learners, however, have difficulties interacting due to technology barriers and attitude. These difficulties affect their feeling of well-being.